Seed quality and storage performance in mungbean and peanut : a thesis presented in partial fulfilment of the requirement for the degree of Master of Agricultural Science in Seed Technology, at Massey University, Palmerston North, New Zealand - Supradith, Uraiwan (Massey University, 1996)
Five seedlots of mungbean and three seedlots of peanut were assessed for seed quality using six standard laboratory tests ie. purity analysis, seed moisture content, germination, seed health, and two vigour tests (accelerated ageing, and conductivity (electrolyte leakage)). These testing methods were valuable as the results allowed distinction of quality differences between seedlots which were used to explain the possible cause or causes of poor quality in each seedlot, eg. high seed moisture content, low viability or vigour, mechanical damage, or fungal infection. The three highest quality seedlots of mungbean (lot 1 cv. Chinese, lot 2 cv. Berken, and lot 3 cv. Regur) and one seedlot of peanut (cv. Spanish White) were identified (germinations 88, 94, 94 and 72 percent before, and 55, 51,66 and 67 percent after accelerated ageing), and selected to use in a subsequent seed storage experiment. Seeds were stored under different conditions involving two seed moisture contents (8.6% and 13.4% for mungbean, and 6.6% and 11.5% for peanut), two storage containers (in aluminium foil packets representing sealed storage, and muslin cloth bags representing open storage) and various temperature/ relative humidity regimes (30°C/95%RH and 20°C/75%RH for mungbean, and 30°C/50%RH. 20°C/75%RH. 5°C/85%RH . and 30°C/95%RH (open storage only) for peanut). Effect of initial seed moisture content or relative humidity, packaging and temperature on seed moisture content, germination percentage, conductivity leachate and seed health of each lot was studied at two monthly intervals during an up to eight months storage period. In all cases, deteriorative changes were higher in open storage at high relative humidity (95%) at 30°C than at lower level relative humidity and temperature regimes. At 30°C/95%RH. seed moisture content of both mungbean and peanut seed open stored initially at low and high moisture content increased markedly to equilibrium with the prevailing relative humidity (15-18.4%SMC in mungbean and 12.4-12.7%SMC in peanut at 2 months storage). Under these conditions all seed all seedlots lost germination after one month (peanut) or six months (mungbean) and loss of electrolytes from seeds into steep water also increased markedly with increasing storage time. Levels of infection by field fungi decreased rapidly with a concomitant rapid increase in invasion of storage fungi, such as Aspergillus glaucus, A. flavus, A. candidus, A. ochraceus A. niger and Penicillium spp. Open stored dry and wet seedlots at lower temperatures/relative humidities of 20°C/75%RH for mungbean, and 30°C/50%RH. 20°C/75%RH, or 5°C/85%RH for peanut, reached equilibrium moisture contents oft 11.3-12.7%, 3.8, 6.5, and 7.2% after 8 months storage, respectively. Mungbean seed germination and vigour was maintained appreciably for 8 months, while peanut seed stored at an initially high moisture content showed a marked decrease in quality, particularly at 30°C. Fungal infection was generally low. Throughout the storage period seed moisture content in sealed storage at all temperatures did not change from initial levels (8.6% or 13.4% in mungbean and 6.6% or 11.5% in peanut). Initial seed moisture content greatly affected seed germination, conductivity leachate and fungal infection, particularly in peanut seeds. Loss of peanut seed germination and seed vigour both increased with increasing seed moisture content and storage temperature. Peanut seeds stored at a higher initial level (11.5%SMC) lost all germination after 2 months storage at 30°C, after 6 months at 20°C and retained near initial levels of germination after 8 months at 5°C. In mungbean seeds stored at 13.5% SMC, seed germination and vigour were affected after 8 months storage at 30°C, particularly in poorer quality lots. The main storage fungal infection was A glaucus but at low levels in all cases. Deteriorative changes were more rapid in initially poorer quality lots than in initially higher quality lots of both mungbean and peanut seed.
Keywords: Mung bean; Peanuts; Seeds -- Quality; Seeds -- Viability